Method for producing glass fiber reinforced polyester resin composition
The method stabilizes the production of high glass fiber content polyester resin pellets by controlling temperature and pressure in a twin-screw extruder, addressing strand breakage and improving pellet quality for continuous production.
Patent Information
- Application Number
- JP2024516130
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-22
- Filing Date
- 2023-03-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-03-10
AI Technical Summary
Glass fiber-reinforced polyester resin compositions with high glass fiber content experience strand breakage during extrusion, leading to reduced productivity and poor pellet quality due to long pellets and chips, which disrupt the molding process.
A manufacturing method using a twin-screw extruder with specific temperature and pressure settings, including a high die holder temperature, low second kneading section temperature, and controlled strand cutting temperature, to maintain shear viscosity within a targeted range, thereby suppressing strand breakage and improving pellet quality.
Enables continuous and stable production of high-quality glass fiber-reinforced polyester resin pellets with reduced long pellets and chips, enhancing productivity and molding stability.
Smart Images

Figure 0007601281000004 
Figure 0007601281000005 
Figure 0007601281000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a glass fiber-reinforced polyester resin composition, and more particularly to a method for producing a glass fiber-reinforced polyester resin composition containing a high concentration of glass fibers by using a twin-screw extruder, which suppresses strand breakage, enables continuous and stable production, has high productivity, and produces pellets that maintain a good pellet shape. [Background technology]
[0002] Polyester resins, such as polybutylene terephthalate resin and polyethylene terephthalate resin, are widely used, mainly for injection molding, in various electric and electronic parts, machine parts, automobile parts, etc. In particular, glass fiber-reinforced polyester resin compositions containing a high content of glass fiber are excellent in mechanical strength, heat resistance, chemical resistance, etc., and are used as parts in the fields of automobiles and electric and electronic equipment, etc.
[0003] Patent Document 1 describes a resin composition in which 5 to 80% of glass fiber is blended with polybutylene terephthalate resin, and Patent Document 2 describes a glass fiber-reinforced polyester resin composition in which 100 parts by mass of polyester resin is blended with 10 to 150 parts by mass of glass fiber.
[0004] However, when a polyester resin composition containing glass fibers at a high concentration of 40% by mass or more is extruded from a die in a twin-screw extruder, strand breakage is likely to occur. This reduces productivity, and when the broken strands are fed into a pelletizer, they overlap with each other, disturbing the flow of the strands and easily generating long pellets. In addition, the strands are not easily cut, the cross section of the pellets is not sharp, and more chips are generated. This tendency becomes more pronounced as the glass fibers are more concentrated. When the long pellets or chips are molded in an injection molding machine, they are likely to cause poor plasticization, which increases the metering time, stops the injection molding machine, and reduces productivity. Usually, strand-cut pellets are cylindrical or elliptical, but if the flattening ratio of the ellipse increases, plasticization may become unstable. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 51-7702 [Patent Document 2] JP 2006-16577 A Summary of the Invention [Problem to be solved by the invention]
[0006] The object (purpose) of the present invention is to suppress breakage of strands emerging from a die when a glass fiber-reinforced polyester resin composition containing a high content of glass fiber is produced using a twin-screw extruder, to enable continuous and stable production, to suppress the generation of long pellets, and to suppress the generation of chips. [Means for solving the problem]
[0007] As a result of extensive investigations conducted by the present inventors to solve the above-mentioned problems, it was found that when a polyester resin composition containing a high content of glass fibers, 40 to 70 mass %, is produced using a twin-screw extruder, the viscosity of the resin composition becomes high. However, by adjusting the shear viscosity to 400 to 2000 Pa s (265°C, 91 / sec) and setting the die pressure during extrusion through a die to a range of 2 to 9 MPa, strand breakage can be suppressed, continuous stable production can be achieved, and the generation of long pellets and chips can be significantly suppressed, thereby completing the present invention. It was also found that the temperature of the die holder is preferably set to a high temperature of 260 to 340°C, and that the temperature of (B) the second kneading section in which the glass fiber is kneaded after the side feed is set to a low temperature of 150 to 220°C, and that the strand temperature when cutting the strands with the pelletizer is preferably set to 100 to 150°C. The present invention relates to the following production method.
[0008] 1. A method for producing a glass fiber reinforced polyester resin composition comprising (A) 10 to 60 mass% of polyester resin, (B) 40 to 70 mass% of glass fiber, and (C) 0 to 50 mass% of other polymers or additives (the total of each component being 100 mass%), using a twin-screw extruder, wherein the glass fiber reinforced polyester resin composition has a shear viscosity of 400 to 2000 Pa s at 265°C and 91 / sec, The method comprises a first step of kneading (A) polyester resin and (C) other polymers or additives in a first kneading section, a second step of adding (B) glass fiber downstream of the first kneading section and kneading the resulting mixture in a second kneading section, a third step of reducing the pressure in a vent downstream of the second kneading section to remove volatile matter and increase the pressure, and extruding the mixture through a die attached to a die holder, and a fourth step of water-cooling the strands discharged from the die and cutting them with a pelletizer. A method for producing a glass fiber-reinforced polyester resin composition, comprising: in the third step, increasing the pressure at the tip of the screw and extruding the resin so that the resin pressure inside the die when it leaves the die is 2 to 9 MPa. 2. The manufacturing method according to the above item 1, wherein the temperature of the die holder in the third step is 260 to 340°C. 3. The method according to 1 or 2 above, wherein the cylinder temperature of the second kneading section in the second step is 150 to 220°C. 4. The manufacturing method according to the above 1, wherein the strand temperature when cutting the strands with a pelletizer in the fourth step is 100 to 150°C. Effect of the Invention
[0009] According to the production method of the present invention, a glass fiber reinforced polyester resin composition (pellet) containing a high content of glass fibers can be produced while suppressing strand breakage, enabling continuous and stable production, and significantly suppressing the generation of long pellets and chips. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a conceptual diagram showing an example of a process from a twin-screw extruder to a pelletizer used in the present invention. [Diagram 2] FIG. 2 is a conceptual diagram of a screw configuration of an extruder used in the Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below with reference to embodiments and examples, but the present invention is not limited to the embodiments and examples shown below, and can be modified as desired without departing from the gist of the present invention. In this specification, the symbol "to" is used to mean that the numerical values before and after the symbol are included as the lower and upper limits.
[0012] In the production method of the present invention, a glass fiber reinforced polyester resin composition consisting of (A) 10 to 60 mass % of polyester resin, (B) 40 to 70 mass % of glass fiber, and (C) 0 to 50 mass % of other polymers or additives is produced in a twin-screw extruder.
[0013] The extruder used in the present invention is a vented twin-screw extruder, preferably an intermeshing type co-rotating twin-screw extruder having two screws rotating in the same direction inside a barrel, and preferably having a kneading section consisting of a plurality of kneading disks disposed midway between the screws in a mutually intermeshing form.
[0014] As shown in Figure 1, a vented twin-screw extruder has a cylinder equipped with a main raw material hopper 1, an open vent 2, a side feed hopper 3, and a reduced pressure vent 4, and a die holder 8 at the tip via a flange 6. The screw inside the cylinder is driven and rotated by a motor 16 via a screw connection part 14 and a gear box 15. A ring plate and a breaker plate are connected between the flange 6 and the die holder 8 to prevent resin leakage. The resin is spread by this die holder and discharged as a strand from the die (which has multiple nozzles). Usually, the resin is spread laterally in the die holder and discharged as a strand 10 from multiple nozzles arranged laterally, called a flat die. The flange 6 may also be called a hinge plate. The die holder may also be called a die plate. The flange 6 (or hinge plate) and the die holder 8 (or die plate) together are generally called a die head. In order to stably produce a glass fiber reinforced polyester resin composition, that is, to suppress breakage of the strands, the temperature of the die holder is also important.
[0015] (A) Polyester resin and (C) other polymers or additives are supplied from a main raw material hopper 1 and kneaded in the first kneading section (first step). (B) Glass fiber is side-fed from a side feed hopper 3 located downstream of the first kneading section and kneaded in the second kneading section (second step). Next, in the downstream section of the second kneading section, the pressure is reduced at a vent 4 to remove volatile matter and increase the pressure, and the material is extruded from a die attached to a die holder 8 (third step). The strands 10 emerging from the die are then water-cooled and cut by a pelletizer 11 (fourth step), yielding pellets 12 of the resin composition.
[0016] In the first step, (A) polyester resin and (C) other polymers or additives are fed from a main raw material hopper 1 into an extruder, and are heated, kneaded, and melted by a screw. A first kneading section made up of a plurality of kneading discs is formed midway through the screw. The first kneading section is a kneading section in which (A) polyester resin and (C) other polymers or additives are kneaded after being added, and refers to a kneading section before (B) glass fiber is added. The screw configuration is preferably a combination of two or more of R kneading discs, N kneading discs, L kneading discs, L screws, seal rings, mixing screws, or rotor screws, and the length is preferably 5.0 to 9.0D (D is the cylinder diameter). The first kneading section is a kneading section in which (A) polyester resin and (C) other polymers or additives are kneaded after being added, and refers to a kneading section before (B) glass fiber is added.
[0017] This first kneading section may be integrated into one, or may be divided into several sections. That is, the first kneading section may also be divided and a feed screw may be inserted between the sections. Even when divided, it is preferable that the total length of the kneading section is in the range of 5.0 to 9.0D.
[0018] The R kneading disc (hereinafter sometimes referred to as R) is a progressive kneading disc element, which usually has two or more blades, and the blade twist angle θ is preferably 10 degrees to 75 degrees. By setting the blades at a predetermined angle in this way, a pseudo-screw structure is formed, which applies a strong shearing force while sending out the resin in the feeding direction, forming a zone where kneading takes place. The L kneading disc (hereinafter sometimes referred to as L) is a reverse kneading disc element, and usually has two or more blades, and the twist angle θ of the blade is preferably -10 degrees to -75 degrees. The reverse kneading disc element is an element that has the ability to block the incoming resin or to increase pressure by acting in the direction of sending the incoming resin back, and by providing it downstream of the element that promotes kneading, it blocks the resin and exerts a strong kneading effect. The N kneading disc (hereinafter sometimes referred to as N) is an orthogonal kneading disc element, which usually has two or more blades and a twist angle θ of the blades of 75 degrees to 105 degrees. Since the blades are installed offset by approximately 90 degrees, the resin delivery force is weak but the kneading force is strong.
[0019] The L screw is a reverse feed screw, the seal ring restricts the flow upstream by using the gaps in the seal ring section, the mixing screw is a screw element with the screw crests (flight section) cut out, and the rotor screw is a screw element with one or more grooves on the outer surface.
[0020] Among these, the R kneading disc, the N kneading disc and the L kneading disc are preferred, and a configuration in which a plurality of these are combined is preferred.
[0021] The screw configuration of the first kneading section in the first step is preferably such that an element that promotes kneading is arranged on the upstream side and an element capable of increasing pressure is arranged on the downstream side. Therefore, in the first kneading section, it is preferable to arrange two or more types selected from R, N, and L in the order of R → N → L from the upstream side, and it is also preferable to arrange multiple R, N, and L. In particular, a configuration in which R is arranged upstream, followed by multiple N, and then L is arranged is preferable.
[0022] The screw length of the first kneading section is preferably in the range of 5.0 to 9.0 D, where D is the cylinder diameter, and such a screw length ensures sufficient melt plasticization of the (A) polyester resin and can also prevent decomposition of the resin composition. If the screw length of the first kneading section is shorter than 5.0 D, the melt plasticization of the resin is likely to be insufficient due to insufficient shear, and if it exceeds 9.0 D, localized decomposition of the resin composition tends to progress due to excessive kneading, and the mechanical properties of the composition are likely to be poor.
[0023] After the polyester resin (A) is kneaded and melted in the first step, it is preferably vented through the open vent 2. It is preferable to provide a seal ring downstream of the open vent 2.
[0024] In the second step, after the first step described above, the (B) glass fiber is side-fed from a side feed hopper 3 located downstream of the first kneading section, and the (B) glass fiber and the molten (A) polyester resin are kneaded in the second kneading section. The second kneading section refers to a kneading section in which (B) glass fiber enters and is opened and kneaded. The screw configuration of the second kneading section is preferably a configuration in which one or more of R kneading discs, N kneading discs, L kneading discs, L screws, seal rings, and mixing screws are combined, and kneading with such a screw configuration tends to result in sufficient opening and dispersion of (B) glass fiber. Among the above, a configuration having at least a mixing screw, particularly a forward notched mixing screw and a reverse notched mixing screw, is preferable.
[0025] The screw length of the second kneading section is preferably in the range of 2.5 to 5.0D. This second kneading section may be integrated into one section, or may be divided into several sections. That is, the second kneading section may be divided and a feed screw may be inserted between the sections. In either configuration, the total kneading section length is preferably in the range of 2.5 to 5.0D. By setting the screw length of the second kneading section in this way, the opening and dispersion of the (B) glass fibers is improved, and the strength of the resin composition is likely to be improved.
[0026] The resin temperature (cylinder temperature) in the second step is generally operated at about 260°C, but in the method of the present invention, it is preferable to set the temperature at 150 to 220°C, which is lower than usual. This second kneading section is a process in which (B) glass fiber enters and is kneaded with (A) polyester resin and (C) other polymers or additives, and the resin temperature is likely to rise. By setting the cylinder temperature in this section to a temperature range of 150 to 220°C, which is lower than usual, it is effective in suppressing breakage of the strand 10 when it comes out of the die holder 8. If the temperature is lower than 150°C, the viscosity of the resin is high, the impregnation into (B) glass fiber is not successful, kneading becomes uneven, and the strand is likely to break. On the other hand, if the temperature is higher than 220°C, the resin temperature is likely to become high, pyrolysis gas is likely to be generated, and the strand is likely to break. The resin temperature (cylinder temperature) in the second step is more preferably 160°C or higher and 210°C or lower.
[0027] The screw speed of the twin screw extruder is preferably 250 to 800 rpm, more preferably 300 to 700 rpm. The discharge rate is preferably 200 to 650 kg / h for TEX44αIII, more preferably 250 to 630 kg / h. For extruders of different sizes, the preferred range of discharge rate is proportional to the 2.5th power of the cylinder diameter ratio.
[0028] After the second step, in the third step, the pressure is reduced at the vacuum vent 4 downstream of the second kneading section to remove volatilization, and the pressure is increased, and the mixture is extruded through a die attached to a die holder 8. The degree of vacuum during the reduced pressure and volatilization at the vacuum vent 4 is preferably -0.097 MPa to -0.07 MPa. Here, the degree of vacuum means the gauge pressure.
[0029] In the third step, the pressure is increased at the tip of the screw and the resin is extruded so that the resin pressure inside the die when it leaves the die is 2 to 9 MPa. The resin pressure in the die (also called die pressure) is the resin pressure at the position of the tip of the screw. The pressure at this position is the highest. Usually, a flange is located at this position, and a resin pressure gauge 7 is installed, so that the pressure can be measured over time. The resin pressure in this die is set to 2 MPa or more and 9 MPa or less. (B) glass fibers are usually in a bundle shape when fed, and by setting the resin pressure in the die to 2 MPa or more and 9 MPa or less, the fibers are kneaded together with the resin, and by applying an appropriate pressure, the resin is easily impregnated into the (B) glass fiber bundle, making it possible to perform uniform kneading, and the occurrence of strand breakage can be suppressed. If it is less than 2 MPa, the kneading state of the resin and (B) glass fibers is not uniform, and the strands are likely to break when they come out of the die. A more preferable resin pressure in the die is 2.5 MPa or more, and even more preferably 3 MPa or more. On the other hand, if the resin pressure is too high, the retention area at the tip of the screw becomes long, gas is easily generated by thermal decomposition, and the strands are easily broken by the gas when they come out of the die. The resin pressure is more preferably 8 MPa or less, and further preferably 7 MPa or less.
[0030] The temperature of the die holder 8 is preferably higher than usual, and is preferably 260°C or higher and 340°C or lower. By setting the temperature at such a temperature, it becomes easier to suppress strand breakage. If the temperature is lower than 260°C, the temperature of the die is lower than the resin temperature of the resin composition, and the temperature of the strands at both ends of the die is lower than the temperature of the strand in the center. This causes a difference in viscosity between the strands, making the strands more likely to break. The temperature of the die holder 8 is more preferably 270°C or higher, and even more preferably 280°C or higher. If the temperature exceeds 340°C, gas is more likely to be generated due to heat retention inside the die, and the strands are also more likely to break. The temperature of the die holder 8 is more preferably 330°C or lower, and even more preferably 320°C or lower.
[0031] The second kneading section thermocouple 5 and die holder thermocouple 9 are inserted into the cylinder of the extruder and the die holder 8, respectively, so that the temperatures of the cylinder and die holder can be measured. Furthermore, heaters are built into the cylinder and die holder, so that the temperatures can be controlled. The cylinder temperature and die holder temperature are the temperatures measured by the inserted thermocouples.
[0032] In the fourth step, the strand 10 coming out of the die is water-cooled and cut by a pelletizer 11. The strand temperature during strand cutting is preferably 100°C or higher and 150°C or lower. By setting the temperature at such a level, it becomes easier to suppress the generation of chips and pellets with poor shapes. If the temperature is lower than 100°C, the strand is hard and chips are likely to be generated when cutting by a pelletizer. This makes the plasticization unstable during molding such as injection molding. If the temperature exceeds 150°C, the flattening ratio of the elliptical cylindrical shape of the cut pellets becomes large, which may also cause poor plasticization. The strand temperature during strand cutting is more preferably 110°C or higher and 140°C or lower.
[0033] Glass fiber reinforced polyester resin compositions containing glass fibers at a high concentration tend to break after coming out of the die and before being cooled and strand cut. The resin content is low, the viscoelastic properties are weakened, and the strands lose their toughness, becoming brittle and easily broken. In addition, the amount of glass fibers is large, so fiber bundles with poor opening properties are likely to be generated. Fiber bundles with poor opening properties are likely to become the starting point of breakage when drawn (stretched). Furthermore, if the resin filling in the fiber bundle is low, that part may become the starting point of breakage (insufficient resin impregnation in the glass fiber bundle). And because of the high concentration of glass fibers, the viscosity of the resin increases and the resin temperature tends to rise. This generates pyrolysis gas, which causes the strands to break when coming out of the die. In this way, it is difficult to stably cut the strands due to the decrease in strand toughness, insufficient opening of the glass fiber bundles, insufficient resin impregnation in the glass fiber bundles, gas generation, etc. If the strands break, it is necessary to manually re-feed the strands into the pelletizer. At that time, the flow of the entire strand becomes disturbed, and the strand enters the cutter at an angle, which makes it easy for long pellets to be generated. Furthermore, because the glass fiber is highly concentrated and the strand is hard, the cut surface by the pelletizer is not sharp, but becomes dull, and chips are generated. In order to suppress the generation of chips, it is necessary to raise the strand cut temperature. This makes the cut sharper and reduces the amount of chips. However, if the strand cut temperature is raised too much, the strand becomes soft and is crushed by the pelletizer's take-up roll, and the eccentricity of the elliptical cylindrical pellets increases. The more long pellets and chips there are and the higher the flatness, the more likely it is that poor plasticization will occur when using the pellets for injection molding, resulting in a decrease in productivity. The number of long pellets (usually more than twice the length of the pellets) is preferably 5 or less per 1 kg. The amount of chips is preferably 300 mass ppm or less of the total mass (pellets + chips). The flatness (long axis / single axis) is preferably 1.30 or less.
[0034] The shape of the extrusion die is not particularly limited, and any known die may be used. The diameter of the die hole varies depending on the desired size of the pellets, but is usually about 2 to 5 mm, and preferably about 3 to 4 mm.
[0035] The strand 10 is taken up by a take-up roller, and is brought into contact with water and cooled. The contact with water may be carried through water stored in a cooling water tank 13, or water may be poured onto the strand 10 to bring it into contact with the water, or the strand may be pulled by a mesh belt conveyor and water is sprayed onto it by a water spraying device. It is better for the time between the strand being extruded from the die and being cooled with water or being immersed in water to be short. Usually, it is better for the strand to be immersed in water within 1 second after being extruded from the die.
[0036] The cooled strand is sent by a take-off roller to a pelletizer, where it is cut into pellets.
[0037] In the method of the present invention, the shear viscosity of the glass fiber reinforced polyester resin composition at 265°C and 91 / sec is 400 Pa·s or more and 2000 Pa·s or less. By setting the shear viscosity in the range of 400 to 2000 Pa·s and combining it with each of the above-mentioned steps, strand breakage is suppressed and continuous stable production is possible. If the viscosity is below 400 Pa·s, the elastic properties of the strand are weak and the strand is easily broken. Also, if the viscosity exceeds 2000 Pa·s, the shear heat generation becomes large, the resin temperature rises, thermal decomposition occurs, and the strand is easily broken. A more preferable range is 500 Pa·s or more and 1700 Pa·s or less, and a further more preferable range is 600 Pa·s or more, and preferably 1400 Pa·s or less.
[0038] The shear viscosity is a value measured using a Capillograph (Capillograph 1D2 manufactured by Toyo Seiki Seisakusho Co., Ltd.) with an orifice having a capillary diameter of 1 mm and a capillary length of 3 mm at 265° C. and a shear rate of 91 / sec in accordance with JIS K7199.
[0039] To adjust the shear viscosity within the above range, the amount of (B) glass fiber can be increased to increase the shear viscosity, or decreased to decrease the shear viscosity, or the amount or viscosity of (C) other polymers to be blended, such as styrene polymers or polycarbonate resins, can be adjusted. Alternatively, the viscosity can be adjusted by changing the viscosity of (A) polyester resin.
[0040] Next, the raw material components used in the present invention will be described.
[0041] (A) Polyester resin The (A) polyester resin is a thermoplastic polyester resin, which is a polyester obtained by polycondensation of a dicarboxylic acid compound and a dihydroxy compound, polycondensation of an oxycarboxylic acid compound, or polycondensation of these compounds, and may be either a homopolyester or a copolyester.
[0042] As the dicarboxylic acid compound constituting the (A) polyester resin, an aromatic dicarboxylic acid or an ester-forming derivative thereof is preferably used. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, diphenylisopropylidene-4,4'-dicarboxylic acid, 1,2-bis(phenoxy)ethane-4,4'-dicarboxylic acid, anthracene-2,5-dicarboxylic acid, anthracene-2,6-dicarboxylic acid, p-terphenylene-4,4'-dicarboxylic acid, and pyridine-2,5-dicarboxylic acid. Terephthalic acid is preferably used.
[0043] These aromatic dicarboxylic acids may be used in combination of two or more. As is well known, in addition to the free acids, these may be used in the polycondensation reaction as ester-forming derivatives such as dimethyl esters. In addition, small amounts of these aromatic dicarboxylic acids can be used in combination with one or more aliphatic dicarboxylic acids such as adipic acid, azelaic acid, dodecanedioic acid, and sebacic acid, and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.
[0044] Examples of dihydroxy compounds constituting the (A) polyester resin include aliphatic diols such as ethylene glycol, propylene glycol, butanediol, hexylene glycol, neopentyl glycol, 2-methylpropane-1,3-diol, diethylene glycol, and triethylene glycol, alicyclic diols such as cyclohexane-1,4-dimethanol, and mixtures thereof. In addition, if the amount is small, one or more long-chain diols having a molecular weight of 400 to 6,000, such as polyethylene glycol, poly-1,3-propylene glycol, and polytetramethylene glycol, may be copolymerized. Additionally, aromatic diols such as hydroquinone, resorcin, naphthalenediol, dihydroxydiphenyl ether, and 2,2-bis(4-hydroxyphenyl)propane can also be used.
[0045] In addition to the above-mentioned bifunctional monomers, a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, or trimethylolpropane may be used in combination to introduce a branched structure, or a monofunctional compound such as a fatty acid may be used in combination to adjust the molecular weight.
[0046] The polyester resin (A) is usually a polycondensation product of dicarboxylic acid and diol, i.e., 50% by mass or more, preferably 70% by mass or more of the total resin is made of this polycondensation product. The dicarboxylic acid is preferably an aromatic dicarboxylic acid, and the diol is preferably an aliphatic diol.
[0047] Among them, polyalkylene terephthalates in which 95 mol % or more of the acid component is terephthalic acid and 95 mass % or more of the alcohol component is an aliphatic diol are preferred. Representative examples are polybutylene terephthalate resin and polyethylene terephthalate resin. These are preferably close to homopolyesters, that is, 95 mass % or more of the entire resin is composed of terephthalic acid components and 1,4-butanediol or ethylene glycol components.
[0048] The (A) polyester resin preferably has a main component (that is, 50% by mass or more) of polybutylene terephthalate resin or polyethylene terephthalate resin, and particularly preferably polybutylene terephthalate resin.
[0049] The (A) polyester resin preferably has an intrinsic viscosity of 0.60 dl / g or more and less than 1.0 dl / g, more preferably 0.60 dl / g or more and less than 0.95 dl / g, and even more preferably 0.65 dl / g or more and less than 0.95 dl / g. If an intrinsic viscosity lower than 0.60 dl / g is used, the mechanical strength of the resulting resin composition tends to be low, the hydrolysis resistance tends to be poor, and the heat shock resistance tends to be low, while if the intrinsic viscosity is 1.0 dl / g or more, it tends to be difficult to obtain good fluidity.
[0050] The intrinsic viscosity of the polyester resin is a value measured at 30° C. in a mixed solvent of 1,1,2,2-tetrachloroethane and phenol in a 1:1 (mass ratio).
[0051] The amount of terminal carboxyl groups in the (A) polyester resin may be appropriately selected and determined, but is usually 60 eq / ton or less, preferably 50 eq / ton or less, and more preferably 30 eq / ton or less. If it exceeds 60 eq / ton, gas tends to be generated during melt molding of the resin composition. The lower limit of the amount of terminal carboxyl groups is not particularly set, but is usually 10 eq / ton in consideration of the productivity of the polyester resin production.
[0052] The amount of terminal carboxyl groups in the polyester resin refers to a value obtained by dissolving 0.5 g of polyalkylene terephthalate resin in 25 mL of benzyl alcohol and measuring by titration using a 0.01 mol / l benzyl alcohol solution of sodium hydroxide. The amount of terminal carboxyl groups can be adjusted by any conventionally known method, such as a method of adjusting polymerization conditions such as the raw material charge ratio during polymerization, polymerization temperature, and pressure reduction method, or a method of reacting a terminal blocking agent.
[0053] (B) Glass fiber As the (B) glass fiber, any known glass fiber can be used so long as it is one that is usually used in polyester resins, regardless of the form of the glass fiber when blended, such as A glass, E glass, alkali-resistant glass composition containing a zirconia component, chopped strand, roving glass, master batch of thermoplastic resin and glass fiber, etc. Among them, as the (B) glass fiber used in the present invention, alkali-free glass (E glass) is preferred for the purpose of improving the thermal stability of the resin composition.
[0054] As the (B) glass fiber, it is also preferable to use glass fiber having a deformation ratio of the longitudinal cross section in the range of 2.0 to 6.0. The irregularity ratio of the longitudinal cross section is the ratio of the long axis to the short axis when a rectangle of the minimum area circumscribing the cross section perpendicular to the longitudinal direction of the glass fiber is assumed, and the length of the long side of this rectangle is defined as the long axis and the length of the short side is defined as the short axis.
[0055] (B) The cross-sectional area of the glass fiber in the longitudinal direction is 90 μm 2Ultra 300μm 2 The cross-sectional area is preferably 90 μm or less, and such a cross-sectional area allows the polyester resin to easily become a matrix, which results in improved heat resistance. 2 Super 250μm 2 Less than 90 μm, more preferably 2 Super 200μm 2 The following is the result. The thickness of the (B) glass fiber is not particularly limited, but it is preferable that the minor axis is about 2 to 20 μm and the major axis is about 5 to 50 μm.
[0056] The (B) glass fiber may be treated with a sizing agent or a surface treatment agent. In addition, during the production of the resin composition of the present invention, a sizing agent or a surface treatment agent may be added separately from the untreated glass fiber to perform surface treatment.
[0057] Examples of the sizing agent include resin emulsions such as vinyl acetate resin, ethylene / vinyl acetate copolymer, acrylic resin, epoxy resin, polyurethane resin, and polyester resin. Examples of the surface treatment agent include aminosilane compounds such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-(2-aminoethyl)aminopropyltrimethoxysilane; chlorosilane compounds such as vinyltrichlorosilane and methylvinyldichlorosilane; alkoxysilane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, and γ-methacryloxypropyltrimethoxysilane; epoxysilane compounds such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane; acrylic compounds, isocyanate compounds, titanate compounds, and epoxy compounds.
[0058] These sizing agents and surface treatment agents may be used in combination of two or more kinds, and the amount used (adhering amount) is usually 10 mass% or less, preferably 0.05 to 5 mass%, based on the mass of the (B) glass fiber. By setting the adhering amount to 10 mass% or less, a necessary and sufficient effect can be obtained, and it is economical.
[0059] (B) Two or more types of glass fibers may be used in combination depending on the required characteristics.
[0060] The content of (B) glass fiber is set to a high content of 40 to 70 mass% relative to 100 mass% of the total of (A) polyester resin, (B) glass fiber, and (C) other polymers or additives. If the content of (B) glass fiber is less than 40 mass%, the rigidity is likely to be insufficient, and conversely, if it exceeds 70 mass%, the impact resistance and fluidity are likely to be insufficient, and production is likely to be difficult. The content of (B) glass fiber is more preferably 42 mass% or more, more preferably 65 mass% or less, and even more preferably 60 mass% or less.
[0061] (C) Other polymers or additives are other polymers other than (A) the polybutylene ester resin and / or various other additives.
[0062] Examples of other additives include various resin additives, such as (B) fillers other than glass fiber (talc, glass flakes, mica, kaolin, ceramic beads, clay, zeolite, barium sulfate, titanium oxide, silicon oxide, aluminum oxide, magnesium hydroxide, zinc sulfide, etc.), flame retardants, flame retardant assistants, stabilizers, antioxidants, release agents, ultraviolet absorbers, weathering stabilizers, lubricants, colorants such as dyes and pigments, catalyst deactivators, antistatic agents, foaming agents, plasticizers, crystal nucleating agents, crystallization accelerators, and the like.
[0063] Examples of other polymers include various elastomers; the styrene-based polymers described below; polycarbonate resins; polyolefin resins such as polyethylene resins and polypropylene resins; polyamide resins; polyimide resins; polyetherimide resins; polyphenylene ether resins; polyphenylene sulfide resins; polysulfone resins; and polymethacrylate resins. The other resins may be contained either alone or in any combination and ratio of two or more kinds.
[0064] The amount of (C) other polymers or additives is 0 to 50 mass%, based on 100 mass% of the total of (A) to (C), and is preferably 45 mass% or less, more preferably 40 mass% or less, even more preferably 35 mass% or less, and is preferably 1 mass% or more, more preferably 2 mass% or more, of which 3 mass% or more, 4 mass% or more, and particularly preferably 5 mass% or more.
[0065] Examples of styrene-based polymers include homopolymers of styrene, graft copolymers obtained by polymerizing styrene in the presence of rubber, copolymers of styrene and (meth)acrylonitrile, copolymers of styrene and (meth)acrylic acid alkyl esters, copolymers of styrene, (meth)acrylonitrile and other copolymerizable monomers, and graft copolymers obtained by graft polymerizing styrene and (meth)acrylonitrile in the presence of rubber. Specific examples of the resin include polystyrene (general purpose polystyrene, GPPS), high impact polystyrene (high impact polystyrene, HIPS), acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), styrene-butadiene-styrene copolymer (SBS resin), hydrogenated styrene-butadiene-styrene copolymer (hydrogenated SBS), hydrogenated styrene-isoprene-styrene copolymer (SEPS), styrene-maleic anhydride copolymer (SMA resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), methyl methacrylate-butadiene-styrene copolymer (MBS resin), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS resin), acrylonitrile-acrylic rubber-styrene copolymer (AAS resin), acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin), and styrene-IPN type rubber copolymer, or mixtures thereof.
[0066] Among these, acrylonitrile-styrene copolymers (AS resins), polystyrene (GPPS), high impact polystyrene (HIPS), and acrylonitrile-butadiene-styrene copolymers (ABS resins) are preferred, and acrylonitrile-styrene copolymers (AS resins), polystyrene (GPPS), high impact polystyrene (HIPS), and acrylonitrile-butadiene-styrene copolymers (ABS resins) are particularly preferred.
[0067] As the styrene-based polymer, a styrene-based elastomer can also be used. As the styrene-based elastomer, a block copolymer comprising a polymer block having a vinyl aromatic compound as a polymerization component and a polymer block having a conjugated diene as a polymerization component, and a hydrogenated product thereof are preferable.
[0068] Examples of vinyl aromatic compounds constituting the vinyl aromatic hydrocarbon polymer block include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, pt-butylstyrene, 1,3-dimethylstyrene, lower alkyl-substituted styrene, vinylnaphthalene, vinylanthracene, and other styrene or derivatives thereof. These can be used alone or in combination of two or more.
[0069] Examples of the conjugated diene constituting the conjugated diene block include butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene.
[0070] The styrene-based polymer may be used alone or in combination of two or more kinds. The amount of the styrene-based polymer is preferably 5 to 45% by mass, based on 100% by mass of the total of (A) to (C).
[0071] The polycarbonate resin is preferably an aromatic polycarbonate resin, and specifically, a thermoplastic aromatic polycarbonate polymer or copolymer obtained by reacting an aromatic dihydroxy compound with phosgene or a diester of carbonic acid is used.
[0072] Examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), tetramethylbisphenol A, and the like.
[0073] Preferred examples of polycarbonate resins include polycarbonate resins using 2,2-bis(4-hydroxyphenyl)propane as a dihydroxy compound or 2,2-bis(4-hydroxyphenyl)propane in combination with other aromatic dihydroxy compounds.
[0074] The polycarbonate resin may be a homopolymer consisting of one type of repeating unit, or a copolymer having two or more types of repeating units, in which case the copolymer may be selected from various copolymer forms such as a random copolymer, a block copolymer, etc.
[0075] The molecular weight of the polycarbonate resin is not limited, but the viscosity average molecular weight (Mv) is usually about 10,000 to 100,000, and preferably about 12,000 to 35,000. By making the viscosity average molecular weight equal to or higher than the lower limit of the above range, the mechanical strength can be further improved, making it more preferable for use in applications requiring high mechanical strength.
[0076] The viscosity average molecular weight (Mv) of a polycarbonate resin is a value calculated from the intrinsic viscosity ([η]) obtained by measuring the viscosity of a methylene chloride solution of the polycarbonate resin at 25° C. using an Ubbelohde viscometer, and then using the following Schnell viscosity formula: [η]=1.23×10 -4 Mv 0.83
[0077] The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by either the phosgene method (interfacial polymerization method) or the melting method (ester exchange method) can be used. In addition, polycarbonate resins produced by the melting method and then subjected to post-treatment to adjust the amount of OH groups at the terminals are also preferred.
[0078] In addition, the polycarbonate resin can be not only virgin raw materials, but also aromatic polycarbonate resins regenerated from used products, so-called material recycled aromatic polycarbonate resins. Preferred examples of used products include optical recording media such as optical disks, light guide plates, automobile window glass, automobile headlamp lenses, vehicle transparent parts such as windshields, containers such as water bottles, eyeglass lenses, soundproof walls, glass windows, corrugated sheets, and other building parts. In addition, the recycled polycarbonate resin can be crushed products obtained from non-conforming products, sprues, or runners, or pellets obtained by melting them.
[0079] When a polycarbonate resin is contained, the amount thereof is preferably 5 to 45% by mass, based on 100% by mass of the total of (A) to (C).
[0080] The glass fiber reinforced polyester resin composition produced by the method of the present invention can be used to produce molded articles with high strength, and therefore can fully satisfy the requirements for weight reduction, thinning and strength, and can be used widely in molded articles or parts in, for example, the fields of electric and electronic equipment, office automation equipment such as computers, precision equipment, optical equipment, automobiles and various other industrial fields. EXAMPLES
[0081] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention.
[0082] The raw materials (A) polyester resin, (B) glass fiber, and (C) other polymers used in the examples and comparative examples are as shown in Table 1 below.
[0083] [Table 1]
[0084] In the following Examples and Comparative Examples, a vented intermeshing co-rotating twin screw extruder ("TEX44αIII" manufactured by Japan Steel Works, Ltd., cylinder diameter D=47 mm) was used.
[0085] The screw configuration is shown in Figure 2. C1 was a feed cylinder, C7 and C12 were vent cylinders, C7 was an open vent, C12 was a reduced pressure vent, and C9 was a side feed cylinder. (A) The first kneading section, which melt-kneaded polyester resin and (C) other polymers, was located from C5 to C6, and the screw configuration was RRNNL with 5 paddles at 1D (1D = 44mm). (B) Glass fiber was side fed from C9. (B) The second kneading section, which kneaded glass fiber, was 1D with 5 paddles at R, and three 1D back mixing screws (lead 0.25D) were arranged as shown in Figure 2.
[0086] The first kneading section is the section where (A) polyester resin and (C) other polymers are added and where (B) glass fibers are fed, and the section from C1 to C9 is the first step. Next, (B) the glass fiber enters the extruder, and the mixing section up to the reduced pressure vent is the second mixing section, and from C10 to C11 is the second process. From C12 to C14, including the die holder, until the mixed resin comes out of the die is the third process. Furthermore, the strand coming out of the die is water-cooled and cut with a pelletizer to obtain pellets, which is the fourth process.
[0087] In the following Examples 1 to 11 and Comparative Examples 1 and 2, resin compositions were produced according to the raw material ratios shown in Formulation 1 in Table 1 above.
[0088] Example 1 57.5 kg / h of polybutylene terephthalate resin (PBT2), 45 kg / h of polyethylene terephthalate resin (PET), and 10 kg / h of elastomer (EL) were fed from the main raw material hopper to the C1 feed barrel of the twin-screw extruder "TEX44αIII", and 137.5 kg / h of glass fiber (GF) was fed from the side feed hopper to the C9 side feed cylinder. The total feed rate of the raw materials was 250 kg / h, and the screw rotation speed was 300 rpm.
[0089] The set temperatures of cylinders C2 to C9 and cylinders C12 to C14 were 250°C. The set temperatures of cylinders C10 and C11 in the second kneading section were 170°C. The set temperature of the die holder in the third process was 300°C. The flange temperature was also 300°C, the same as the die holder. In addition, a flat die with a hole diameter of 3.8 mm, a land length of 20 mm, and 10 holes arranged horizontally was used. The resin pressure inside the die at this time was 5.2 MPa. In the following examples and comparative examples, the temperature of the flange was set to be the same as the temperature of the die holder.
[0090] The strand emerging from the die was cooled in a water bath and cut into strands by a pelletizer to obtain elliptical cylindrical pellets with a length of 3 mm. The strand take-up speed of the pelletizer was 40 m / min. The water-cooling distance of the strand was adjusted at this time, and the temperature of the strand at the time of cutting was set to 130°C. The temperature of the strand was measured with an infrared thermometer. This extrusion was continued for one hour. Not a single strand broke during that hour. The size of the obtained elliptical cylindrical pellets was 3.0 mm in length, 3.0 mm in major axis, and 2.4 mm in minor axis (flatness ratio: 1.25), calculated as the number average of 20 pellets. 1 kg of pellets was collected, and the amount of chips was measured using a sieve with 1 mm openings to determine the chip ratio (ppm by mass). The pellets remaining on the sieve (approximately 1 kg) were visually inspected, and the number of long pellets (pellets longer than 6 mm) was counted. These results are shown in the table. The amount of chips was extremely small, with no long pellets. The flatness of the elliptical cylindrical pellets was good at 1.25.
[0091] The obtained pellets were dried at 120°C for 5 hours, and the shear viscosity was measured at a shear rate of 91 / sec at a temperature of 265°C using a Capilograph 1D2 (manufactured by Toyo Seiki Seisakusho Co., Ltd.) with an orifice having a capillary diameter of 1 mm and a capillary length of 3 mm. The shear viscosity was 1020 Pa s. The results are shown in Table 2.
[0092] The strand breakage was evaluated according to the following criteria. A: Strand breakage rate 0 times / hour B: Strand breakage 1-2 times / hour C: Strand breakage frequency: 3-9 times / hour D: Strand breakage 10 or more times / hour The pellet shape was evaluated according to the following criteria. A: Chips ≦300ppm, flatness ≦1.30, and long pellets ≦5 pieces / kg B: Chips > 300ppm or flatness > 1.30 or long pellets > 5 pieces / kg
[0093] Example 2 The same procedure as in Example 1 was carried out except that the die land length was set to 10 mm. The resin pressure at the die portion at this time was 2.8 MPa. The results are shown in Table 2.
[0094] Example 3 The same procedure as in Example 1 was carried out except that the die land length was set to 30 mm. The resin pressure at the die was 7.2 MPa. The results are shown in Table 2.
[0095] Example 4 The same procedure as in Example 1 was carried out except that the temperature of the die holder was set to 270° C. The results are shown in Table 2.
[0096] Example 5 The same procedure as in Example 1 was carried out except that the temperature of the die holder was set to 330° C. The results are shown in Table 2.
[0097] Example 6 The same procedure as in Example 1 was carried out, except that the temperature of the die holder was set to 250° C. The results are shown in Table 2.
[0098] Example 7 The same procedure as in Example 1 was carried out, except that the temperature of the die holder was set to 350° C. The results are shown in Table 2.
[0099] Example 8 The same procedure as in Example 1 was carried out except that the temperature of the second kneading zone was set to 140° C. The results are shown in Table 2.
[0100] Example 9 The same procedure as in Example 1 was carried out except that the temperature of the second kneading section was set to 240° C. The results are shown in Table 2.
[0101] Example 10 The same procedure as in Example 1 was repeated except that the strand cut temperature was 95° C. The results are shown in Table 2. The strand cut temperature was low, and a large amount of chips was generated.
[0102] Example 11 The same procedure as in Example 1 was carried out except that the strand cutting temperature was 155° C. The results are shown in Table 2. The amount of cutting chips was small, but the flattening ratio of the elliptical cylindrical pellets was large.
[0103] Comparative Example 1 The die land length was set to 5 mm, and the experiment was carried out in the same manner as in Example 1. The resin pressure at the die was 1.7 MPa. Strand breakage occurred 16 times during the one-hour experiment. This was not a situation conducive to stable production.
[0104] Comparative Example 2 The die land length was set to 40 mm, and the experiment was carried out in the same manner as in Example 1. The resin pressure at the die was 9.4 MPa. Strand breakage occurred 19 times during the one-hour experiment. This was not a situation conducive to stable production.
[0105] The results are shown in Table 2 below.
[0106] [Table 2]
[0107] In the following Examples 12 to 22 and Comparative Examples 3 and 4, resin compositions were produced using the raw material ratios shown in Recipe 2 in Table 1 above.
[0108] Example 12 50.0 kg / h of PBT1, 75 kg / h of PS, and 12.5 kg / h of PC were fed from the main raw material hopper to the C1 feed barrel of the twin-screw extruder "TEX44αIII", and 112.5 kg / h of glass fiber was fed from the side feed hopper to the C9 side feed cylinder. The total feed amount of the raw materials was 250 kg / h. The same procedure as in Example 1 was repeated except that the screw rotation speed was 370 rpm. The results are shown in Table 3 below. The obtained pellets were dried at 120°C for 5 hours, and the shear viscosity was measured at a shear rate of 91 / sec at a temperature of 265°C using a Capilograph 1D2 (manufactured by Toyo Seiki Seisakusho Co., Ltd.) with an orifice having a capillary diameter of 1 mm and a capillary length of 3 mm. The shear viscosity was 720 Pa s.
[0109] Example 13 The same procedure as in Example 12 was carried out except that the die land length was 10 mm. The resin pressure at the die was 2.6 MPa. The results are shown in Table 3.
[0110] Example 14 The same procedure as in Example 12 was carried out except that the die land length was 30 mm. The resin pressure at the die was 7.1 MPa. The results are shown in Table 3.
[0111] Example 15 The same procedure as in Example 12 was repeated, except that the die holder temperature was 270° C. The results are shown in Table 3.
[0112] Example 16 The same procedure as in Example 12 was carried out, except that the temperature of the die holder was 330° C. The results are shown in Table 3.
[0113] Example 17 The same procedure as in Example 12 was repeated, except that the die holder temperature was 250° C. The results are shown in Table 3.
[0114] Example 18 The same procedure as in Example 12 was carried out except that the temperature of the die holder was 350° C. The results are shown in Table 3.
[0115] Example 19 The same procedure as in Example 12 was repeated except that the temperature of the second kneading zone was 140° C. The results are shown in Table 3.
[0116] Example 20 The same procedure as in Example 12 was carried out except that the temperature of the second kneading section was 240° C. The results are shown in Table 3.
[0117] Example 21 The same procedure as in Example 12 was repeated except that the strand cut temperature was 95° C. The results are shown in Table 3. The strand cut temperature was low, and a large amount of chips was generated.
[0118] Example 22 The same procedure as in Example 12 was repeated except that the strand cut temperature was 155° C. The results are shown in Table 3. The amount of cutting chips was small, but the flattening ratio of the elliptical cylindrical pellets was large.
[0119] Comparative Example 3 The die land length was set to 5 mm, and the experiment was carried out in the same manner as in Example 12. The resin pressure at the die was 1.6 MPa. Strand breakage occurred 14 times during the one-hour experiment. This was not a situation conducive to stable production.
[0120] Comparative Example 4 The die land length was set to 40 mm, and the experiment was carried out in the same manner as in Example 12. The resin pressure at the die was 9.1 MPa. Strand breakage occurred 21 times during the one-hour experiment. This was not a situation conducive to stable production.
[0121] [Table 3] [Industrial Applicability]
[0122] According to the production method of the present invention, it is possible to stably produce high-quality pellets of a glass fiber-reinforced polyester resin composition containing glass fibers at a high concentration. [Explanation of symbols]
[0123] 1: Main raw material hopper 2: Open vent 3: Side feed hopper 4: Decompression vent 5: Second mixing section thermocouple 6: Flange 7: Resin pressure gauge 8: Die holder 9: Die holder thermocouple 10: Strand 11: Pelletizer 12: Pellet 13: Cooling tank 14: Screw connection 15: Gearbox 16:Motor
Claims
1. A method for producing a glass fiber-reinforced polyester resin composition comprising (A) 10 to 60 mass% of polyester resin, (B) 40 to 70 mass% of glass fiber, and (C) 0 to 50 mass% of other polymers or additives (the total of each component is 100 mass%), using a twin-screw extruder, wherein the glass fiber-reinforced polyester resin composition has a shear viscosity of 400 to 2000 Pa s at 265°C and 91 / sec, The method comprises a first step of kneading (A) polyester resin and (C) other polymers or additives in a first kneading section, a second step of adding (B) glass fiber downstream of the first kneading section and kneading the resulting mixture in a second kneading section, a third step of reducing the pressure of the resin in a vent section downstream of the second kneading section to devolatilize it, and extruding the resin from a die attached to a die holder while increasing the pressure, and a fourth step of water-cooling the strands discharged from the die and cutting them with a pelletizer. A method for producing a glass fiber reinforced polyester resin composition, characterized in that in the third step, the pressure is increased at the tip of the screw and the resin is extruded so that the resin pressure in the die when it exits the die is 2 to 9 MPa.
2. The method according to claim 1, wherein the temperature of the die holder in the third step is 260 to 340°C.
3. 3. The method according to claim 1, wherein the cylinder temperature of the second kneading zone in the second step is 150 to 220°C.
4. 2. The method according to claim 1, wherein the strand temperature when the strands are cut by the pelletizer in the fourth step is 100 to 150° C.
Citation Information
Patent Citations
Suiteinarashisochi
JP1976007702A
Cap for producing molding resin composition
JP1997239803A
Method for manufacturing thermoplastic resin pellet
JP2004276598A
Organic electroluminescent material and light-emitting device
JP2006016577A
Polycarbonate resin composition pellet and manufacturing method therefor
JP2015229755A
